STRATEGY FORMULATION IN MANAGEMENT OF SUSTAINABLE ISLAMIC EDUCATIONAL INSTITUTIONS: STRATEGY FORMULATION IN MANAGEMENT OF SUSTAINABLE ISLAMIC EDUCATIONAL INSTITUTIONS - AHMAD JUNAIDI; Sulistyorini Sulistyorini; Agus Zaenul Fitri Agus Zaenul Fitri (As-Sulthan Journal of Education, 2026)
The success of Islamic Educational Institutions depends on leaders’ ability to formulate appropriate and accurate strategies. Through strategy formulation, Institutions can identify their strengths, weaknesses, opportunities, and threats. This study is library research with a qualitative approach. Primary data used is the book